Caracterização limnológica do Lagamar do Cauípe-planície costeira do município de Caucaia-Ce - Queiroz, Ana Maria de (2003)
Limnological research is very scarce in tropical areas, particularly if we consider that of long duration. This research was carried out at the “Lagamar do Cauípe” (a coast plain in Caucaia town, Ceará, Brazil, during the period from June, 2001 to February, 2002, aiming at making a diagnosis about the physical, chemical and environmental characteristics of the lagoon located situated in Lagamar of Cauípe, with the objective of obtaining basic information which enables the implementation of programs of management and proper use of that water resource. We conducted the bathymetry in order to know its morphometry and level of sediment deposition in the future. We conducted sampling of water and sediment in the lagoon and observed the use and occupation of its margins. The parameters analyzed in the water were: temperature, transparency, suspended solids, pH, salinity, electrical conductivity, dissolved oxygen, nitrite, nitrate, total phosphorus, orthophosphate, main cations and anions, total alkalinity, total hardness and chlorophyll a. During the investigation period we observed a small variation in the concentration of the parameters analyzed. The smallest concentrations were obtained at the end of the rain season (June, 2001), and they increased significantly during the dry season (July to December, 2001) and decreased slightly at the beginning of the rain season (February, 2002). We did not observe any significant variation among the sampling stations, so that we can say that the lagoon water tends to be homogeneous. Concerning salinity, the water was considered as fresh water. The average temperature was 28,6°C, with a small annual variation of 3,7°C, which is typical of the tropical aquatic ecosystems. Its pH is slightly acid due to the region’ soils and probably due to the presence of humic compounds. The average electrical conductivity was 285,6 μS/cm. The larger cations presented a sequence typical of an environment influenced by the sea, with the water being considered as chlorinated-sodic. The whole column turned out oxygenated, in spite of the high concentration of suspended solids, because of, mainly, the resuspension of the sediment of the lagoon’ bottom. The presence of suspended solids reduced the transparency of the lagoon water, influencing the concentration of the chlorophyll-a, which presented low concentrations. The values of total alkalinity were low, indicating the small capacity of the lagoon waters to neutralize acids. With relationship to hardness, the waters varied from soft to somewhat hard. The concentrations of total phosphorus were high, with the lagoon being considered as eutrophic. The concentrations of nitrite and nitrate were low, being below the one established by the legislation. We did not observe any significant variations between the surface and bottom samples. The homogeneity of the water column was explained by the small depth of the lagoon, the intensity of the winds, which are steady in the coast area, and the lagoon’ morphology with a lengthened shape and position favorable to the action of the winds of the area. In the sediment’ samples, we conducts trials of texture, organic matter and mercury. The sediments are of the mineral type, having been distinguished in 3 texture facies: medium sand, fine sand and mud. The mercury’ concentration found was low.